Examination of Contextual Variables Across and Within Different Types of Placement for Elementary Students With Complex Support Needs. (December 2022) - Jackson, Lewis; Agran, Martin; Lansey, Kirsten Rebecca; Baker, Dale; Matthews, Somer; Fitzpatrick, Heather; Jameson, Matt; Ryndak, Diane; Burnette, Kristin; Taub, Debbie
Research has begun to identify the breadth and complexity of contextual variables that impact the opportunities, services, and supports students with complex support needs receive across different classroom placements. Indeed, as research has suggested, placement in and of itself may determine the schooling experiences of these students in ways that can enhance or constrain the outcomes of the educational process. This study examined an array of contextual variables in relation to four types of placement in which students with complex support needs might be placed for educational services by their Individualized Education Program teams. Placements were defined in terms of percent of the school day students had access to age-level general education classes, ranging between no access (separate school) to 80% or higher ("inclusive"). The investigation used surveys completed by a national sample of special and general educators and administrators. Completed surveys were obtained for 117 students with complex support needs across all four types of placement. The findings revealed potential relationships between a number of contextual variables and placement, suggesting that: (a) student opportunities and experiences vary systematically in relation to the amount of access they have to general education classrooms and (b) the application of the Least Restrictive Environment process, with its tacit endorsement of segregated settings and specialized programs, may in fact negatively impact the education of many of these students. Implications of these findings and future research needs are discussed.